2017
DOI: 10.1159/000454991
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Biomarker Profiles, Etiology of Chronic Kidney Disease, and Mortality

Abstract: Background: Prognosis in chronic kidney disease (CKD) for adverse outcomes differs substantially based on the etiology of CKD. We examined whether the biomarker profile differed based on CKD etiology and whether they were associated with mortality. Methods: Prospective observational study of 1,157 patients, 663 with diabetic kidney disease (DKD), 273 with glomerulonephritis (GN), and 221 with cystic/interstitial disease (polycystic kidney disease, pyelonephritis or chronic tubulointerstitial nephritis [PCK/TIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…[27][28][29] Eight studies reported associations that could not be extracted or reliably expressed as RRs comparing the top versus bottom third of baseline FGF-23 concentration (see Supplemental Table 4 for results from these and the other excluded studies). [30][31][32][33][34][35][36][37] Of 34 studies included in primary analyses, 17 were in predominantly general population cohorts, 22,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] nine were in patients with CKD not on dialysis, 23,[54][55][56][57][58][59][60][61] and eight in patients on dialysis 24,[62][63][64][65][66][67][68] ( Figure 1). For patients on dialysis, a single large trial (EValuation Of Cinacalcet HCl Therapy to Lower CardioVascular ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Eight studies reported associations that could not be extracted or reliably expressed as RRs comparing the top versus bottom third of baseline FGF-23 concentration (see Supplemental Table 4 for results from these and the other excluded studies). [30][31][32][33][34][35][36][37] Of 34 studies included in primary analyses, 17 were in predominantly general population cohorts, 22,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] nine were in patients with CKD not on dialysis, 23,[54][55][56][57][58][59][60][61] and eight in patients on dialysis 24,[62][63][64][65][66][67][68] ( Figure 1). For patients on dialysis, a single large trial (EValuation Of Cinacalcet HCl Therapy to Lower CardioVascular ...…”
Section: Resultsmentioning
confidence: 99%
“…However, the studies excluded because of inability to convert associations showed positive associations between FGF-23 and disease risks that were similar in size to those observed by the included studies (Supplemental Table 4). [30][31][32][33][34][35][36][37] Furthermore, given the lack of trends across the three population types despite a two-fold increase in the absolute difference in FGF-23 concentration, it is unlikely that individual participant data would identify an important log-linear trend missed by our tabular meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It also improves endothelial function (Tonetti et al, 2007) that may contribute to an increased kidney microcirculation and, hence, more effective filtration. Moreover, periodontal treatment was associated with a decrease in asymmetric dimethylarginine (ADMA) level 6 months after periodontal treatment (Almeida et al, 2017), a predictor of progression of renal disease, and of all-cause, and particularly, cardiovascular risk and mortality (Langsford et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether or not moderate levels of albuminuria by itself are an early predictor of DKD and its progression remains controversial [ 17 , 47 , 48 ]. This may be due to multiple pathophysiological factors which are part of the constellation of DKD (interstitial damage, vascular and/or glomerular) [ 49 ] and reinforces the need to search for more sensitive and specific biomarkers [ 50 , 51 ]. Nevertheless, albuminuria, together with eGFR, remains useful for monitoring kidney function [ 38 , 52 ].…”
Section: Diagnosis Of Dkdmentioning
confidence: 99%